#### Answer

$\sqrt[4]{27}\cdot \sqrt[4]{3} = \sqrt[4]{81}=3,-3$

#### Work Step by Step

$\sqrt[4]{27}\cdot \sqrt[4]{3} = \sqrt[4]{27 \cdot 3} = \sqrt[4]{81}=3,-3$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\sqrt[4]{27}\cdot \sqrt[4]{3} = \sqrt[4]{81}=3,-3$

$\sqrt[4]{27}\cdot \sqrt[4]{3} = \sqrt[4]{27 \cdot 3} = \sqrt[4]{81}=3,-3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.